Dephosphorylation of Y228 and Y217 and phosphorylation of Y335 in p120 catenin activate convergent extension during zebrafish gastrulation. Issue 12 (19th September 2022) - Shan, Botao; Horton, Emma C.; Xu, Shan C.; Huntington, Kelsey E.; Kawano, Dane K.; Mendoza, Clemence L.; Lin, Laura; Stafford, Christopher M.; Allen, Emili D.; Huang, Joyce; Nakahara, Hiroko; Greenstein, Lewis E.; et al.
Abstract: Background: The cadherin‐associated protein p120 catenin regulates convergent extension through interactions with cadherin proteins, Cdc42, and Rac1, as we previously showed in zebrafish ( Danio rerio ). Phosphorylation of p120 catenin changes the nature of its activity in vitro but is virtually unexplored in embryos. We used our previously developed antisense RNA splice‐site morpholino targeted to endogenous p120 catenin‐δ1 to cause defects in axis elongation probing the functions of three p120 catenin tyrosine‐phosphorylation sites in gastrulating zebrafish embryos. Results: The morpholino‐induced defects were rescued by co‐injections with mouse p120 catenin‐δ1‐3A mRNAs mutated at residues Y228 and Y217 to a non‐phosphorylatable phenylalanine (F) or mutated at residue Y335 to a phosphomimetic glutamic acid (E). Co‐injection of the complementary mutations Y228E, Y217E, or Y335F mRNAs partially rescued embryos whereas dual mutation to Y228E‐Y217E blocked rescue. Immunopurification showed Y228F mutant proteins preferentially interacted with Rac1, potentially promoting cell migration. In contrast, the phosphomimetic Y228E preferentially interacted with E‐cadherin increasing adhesion. Both Y228F and Y335F strongly bind VAV2. Conclusions: p120 catenin serves dual roles during gastrulation of zebrafish. Phosphorylation and dephosphorylation of tyrosine residues Y217, Y228, and Y335 precisely balance cell adhesion and cell migration to facilitate somite compaction and axis elongation. Key Findings: Knockdown of zebrafish p120 catenin‐δ1 with a morpholino blocks migration of presomitic mesoderm and extension of the dorsal axis. We compared rescue of morphology by injecting mouse p120 catenin‐δ1‐3A (CTNND1‐3A) mRNAs mutated to phosphomimetic (E) and nonphosphorylatable (F) versions of tyrosine residues. Mutations to Y228F, Y228E, Y217F, or Y335E rescued morphology; mutation to Y217E, or Y335F mRNAs only partially rescued; and dual mutation to Y228E‐Y217E blocked rescue. Immunopurification showed Y228F mutant proteins preferentially binding to Rac1, potentially promoting cell migration, and the Y228E protein preferentially binding with E‐cadherin increasing adhesion. Both Y228F and Y335F bound strongly to VAV2. We show the importance of phosphorylation state for regulating adhesion and mesodermal cell migration in early vertebrate morphogenesis.